At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

3s+2t−3 =c
−7s−5t =4



Sagot :

Answer:

c=

−4

3

s−t+

−4

3

Step-by-step explanation:

Let's solve for c.

3s+2t−3c−7s−5t=4

Step 1: Add 4s to both sides.

−3c−4s−3t+4s=4+4s

−3c−3t=4s+4

Step 2: Add 3t to both sides.

−3c−3t+3t=4s+4+3t

−3c=4s+3t+4

Step 3: Divide both sides by -3.

−3c

−3

=

4s+3t+4

−3

c=

−4

3

s−t+

−4

3